Question 24 (OR 1 st question)
If A = [3 1 2 3 2 -3 2 0 -1], find A ^{ –1 }
Hence, solve the system of equations:
3x + 3y + 2z = 1
x + 2y = 4
2x – 3y – z = 5
Get live Maths 1-on-1 Classs - Class 6 to 12
CBSE Class 12 Sample Paper for 2019 Boards
Question 1 Important
Question 2
Question 3
Question 4 (Or 1st) Important
Question 4 (Or 2nd)
Question 5
Question 6
Question 7 Important
Question 8 (Or 1st) Important
Question 8 (Or 2nd)
Question 9
Question 10 (Or 1st) Important
Question 10 (Or 2nd)
Question 11 Important
Question 12 (Or 1st)
Question 12 (Or 2nd)
Question 13 (Or 1st) Important
Question 13 (Or 2nd)
Question 14 Important
Question 15
Question 16 (Or 1st)
Question 16 (Or 2nd) Important
Question 17
Question 18
Question 19 Important
Question 20 Important
Question 21 (Or 1st)
Question 21 (Or 2nd) Important
Question 22
Question 23 Important
Question 24 (Or 1st) You are here
Question 24 (Or 2nd) Important
Question 25
Question 26 (Or 1st) Important
Question 26 (Or 2nd)
Question 27 (Or 1st) Important
Question 27 (Or 2nd) Important
Question 28
Question 29 Important
CBSE Class 12 Sample Paper for 2019 Boards
Last updated at March 23, 2023 by Teachoo
Question 24 (OR 1 st question)
If A = [3 1 2 3 2 -3 2 0 -1], find A ^{ –1 }
Hence, solve the system of equations:
3x + 3y + 2z = 1
x + 2y = 4
2x – 3y – z = 5
Get live Maths 1-on-1 Classs - Class 6 to 12
Question 24 (OR 1st question) If A = [■8(3&1&[email protected]&2&−[email protected]&0&−1)], find A–1 Hence, solve the system of equations: 3x + 3y + 2z = 1 x + 2y = 4 2x – 3y – z = 5 For our equation [■8(3&3&[email protected]&2&[email protected]&−3&−1)][■8(𝑥@𝑦@𝑧)] = [■8([email protected]@5)] i.e. (𝐴^𝑇)X = B X = 〖(𝐴^𝑇)〗^(−1) 𝐵 X = 〖(𝐴^(−1))〗^𝑇 𝐵 (Because 〖(𝐴^𝑇)〗^(−1) = 〖(𝐴^𝑇)〗^(−1)) Here, A = [■8(3&1&[email protected]&2&−[email protected]&0&−1)] , X = [■8(𝑥@𝑦@𝑧)] & B = [■8([email protected]@5)] Finding A–1 We know that A-1 = 1/(|A|) adj (A) Calculating |A|= |■8(3&1&[email protected]&2&−[email protected]&0&−1)| = 3(−2 + 0) − 1 (–3 + 6) + 2 (0 – 4) = –6 – 3 – 8 = −17 Since |A|≠ 0 ∴ The system of equation is consistent & has a unique solutions Now finding adj (A) adj A = [■8(A11&A12&[email protected]&A22&[email protected]&A32&A33)]^′ = [■8(A11&A21&[email protected]&A22&[email protected]&A23&A33)] A = [■8(3&1&[email protected]&2&−[email protected]&0&−1)] 𝐴11 = −2 + 0 = –2 𝐴12 = −[−3−(−6)] = − (−3+ 6) = −3 𝐴13 = 0 − 4 = – 4 𝐴21 = –[−1−0] = 1 𝐴22 = −3 – 4 = –7 𝐴23 = –[0−2] = 2 𝐴31 = −3−4= –7 𝐴32 = –[−9−6] = 15 𝐴33 = 6−3 = 3 Thus adj A = [■8(−2&1&−[email protected]−3&−7&[email protected]−4&2&3)] & |A| = –17 Now, A-1 = 1/(|A|) adj A A-1 = 1/(−17) [■8(−2&1&−[email protected]−3&−7&[email protected]−4&2&3)] = 1/17 [■8(2&−1&[email protected]&7&−[email protected]&−2&−3)] Now, X = 〖(𝐴^(−1))〗^𝑇 𝐵 [■8(𝑥@𝑦@𝑧)] = 1/17 [■8(2&−1&[email protected]&7&−[email protected]&−2&−3)]^′ [■8([email protected]@5)] [■8(𝑥@𝑦@𝑧)] = 1/17 [■8(2&3&[email protected]−1&7&−[email protected]&−15&−3)][■8([email protected]@5)] " " [■8(𝑥@𝑦@𝑧)]" =" 1/17 [█(2(1)+3(4)+4(5)@−1(1)+7(4)+(−2)(5)@7(1)+(−15)(4)+(−3)(5))] " " [■8(𝑥@𝑦@𝑧)]" =" 1/17 [■8([email protected]−1+28−[email protected]−60−15)] " " [■8(𝑥@𝑦@𝑧)]" =" 1/17 [■8([email protected]@−68)] " " [■8(𝑥@𝑦@𝑧)]" =" [■8([email protected]@−4)] "∴ x = 2, y = 1 and z = "–4